The Bigger the Children, the Bigger the Worries: Are Preschoolers and Adolescents Affected Differently by Family Instability with Regard to Non-cognitive Skills? - Frauke H. Peter; C. Katharina Spiess (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Substantial research on the relationship between family structures and child outcomes represents a considerable part of the literature. However, family structure provides a rather static view of the relationship of children's living arrangements and their well-being, revealing hardly anything about the stability of a family for a longer period. This paper focuses on the impact of family instability on children. In light of human capital accumulation, we hypothesize that a stable family (either a two parent or a single parent family) might be beneficial for child outcomes, in particular for non-cognitive skills. We use skills, such as socio-emotional behavior or locus of control, as our primary measure of child outcomes. The paper focuses on the potential impact of family instability occurring at different childhood stages on non-cognitive skills of preschoolers (aged five to six) and of adolescents (aged seventeen). Our analysis is based on data from the German Socio-Economic Panel Study (SOEP). Family instability is defined by yearly observed maternal partnership variations. Our results suggest that differences in family stability account for some of the gradient in social-behavioral difficulties for preschool children. By using sibling differences for our adolescents' sample, we find that multiple partnership transitions experienced early in life are negatively correlated with non-cognitive skills in adolescence, e.g., such adolescents are less likely to be active or self-determined in life.
Keywords: J10; J12; J13; 330; Child development; family dynamics; locus of control; non-cognitive skills; Kinder; Jugendliche; Familiensoziologie; Selbstevaluation; Kognition; Schätzung; Deutschland